Effect of Environmental Conditions and Human Activities on Vertical Distribution Characteristics of Bacterial Communities in Shallow Lakes Sediments - Yan, W.M.; Liu, L.; Fang, Z.J.; Qian, B.; Zhang, Y.; Gao, H.Q.; Wu, T.F. (Asian Journal of Chemistry, 2012)
The aim of this study was to evaluate the microbial community structure in different sediment layers in the lakes such as Jiulongkou lake, Dazong lake and Wujindang lake located in Lixia river regions (regions between Liyunhe canal and Xiahe river) of the Huai river basin under the stress of nature and human activities. The diversity and dominance of bacterial community using the 16S rDNA cloning-sequencing approach were determined within the appropriate sediment layers. Quantity software and UPGAMA cluster analysis were used to analyze the vertical distribution characteristics of bacterial community in combination with the related environmental data. The results show that there is an abundant diversity of bacteria in the lake sediments in Lixia river regions and there are differences in the abundance of longitudinal bacteria at different layers. The abundance of the middle layer is comparatively high, while the upper layer is lower and the lower layer is the lowest. Although there are some common clones in the sediments at different layers, the composition of predominant bacteria at different layers apparently varies. The experimental results show that the human activities have considerable impact on the environment of sediments in the downstream lakes and affect the bacterial community structure of sediments.